Biochar in the Agroecosystem–Climate-Change–Sustainability Nexus - Nair, Vimala D.; Nair, P. K. Ramachandran; Dari, Biswanath; Freitas, Andressa M.; Chatterjee, Nilovna; Pinheiro, Felipe M. (Frontiers in Plant Science, 2017)
Interest in the use of biochar in agriculture has increased exponentially during the past decade. Biochar, when applied to soils is reported to enhance soil carbon sequestration and provide other soil productivity benefits such as reduction of bulk density, enhancement of water-holding capacity and nutrient retention, stabilization of soil organic matter, improvement of microbial activities, and heavy-metal sequestration. Furthermore, biochar application could enhance phosphorus availability in highly weathered tropical soils. Converting the locally available feedstocks and farm wastes to biochar could be important under smallholder farming systems as well, and biochar use may have applications in tree nursery production and specialty-crop management. Thus, biochar can contribute substantially to sustainable agriculture. While these benefits and opportunities look attractive, several problems and bottlenecks remain to be addressed before widespread production and use of biochar becomes popular. The current state of knowledge is based largely on limited small-scale studies under laboratory and greenhouse conditions. Properties of biochar vary with both the feedstock from which it is produced and the method of production. The availability of feedstock as well as the economic merits, energy needs, and environmental risks – if any – of its large-scale production and use remain to be investigated. Nevertheless, available indications suggest that biochar could play a significant role in facing the challenges posed by climate change and threats to agroecosystem sustainability.